Dynamic multi-domain virtual optical network deployment with heterogeneous control domains [invited] - Vilalta, Ricard; Munoz, Raul; Casellas, Ramon; Martinez, Ricardo; Shuping Peng; Channegowda, Mayur; Vlachogiannis, Tasos; Nejabati, Reza; Simeonidou, Dimitra; Xiaoyuan Cao; Tsuritani, Takehiro; Morita, Itsuro (Journal of optical communications and networking, 2015)
We propose a multi-domain resource broker to dynamically provision multi-domain virtual optical networks across heterogeneous control domains (i.e., GMPLS and OpenFlow) and transport (i.e., optical packet switching and elastic optical networks) technologies. We have designed, implemented, and experimentally evaluated the multi-domain resource broker in an international testbed across Spain, the UK, and Japan.